Caries-risk profiles in Italian adults using computer caries assessment system and ICDAS - Giovanna CARTA; Maria Grazia CAGETTI; Fabio COCCO; Silvana SALE; Peter LINGSTRÖM; Guglielmo CAMPUS (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to examine the correlation among socio-behavioral factors, caries status and caries risk, calculated through Cariogram, in an adult population. Four hundred eighty subjects (mean age 40.73, SE ± 0.33) randomly selected from the municipal electoral registry consented to participate in the survey. Subjects were examined, and the International Caries Detection Assessment System (ICDAS) index was registered. A highly structured questionnaire was submitted to investigate (1) personal data (i.e., age, gender, educational level, job categorization), (2) life-style behavior (i.e., smoking and dietary habits), and (3) oral health behavior (i.e., tooth brushing, use of fluoride and dental check-up frequency). An evaluation of the mutans streptococci concentration in saliva was also performed. Information on caries-related factors was entered into the Cariogram in order to generate an individual caries risk profile for each subject. Multinomial logistic regression was performed using Cariogram levels as the dependent variable. The possible correlated variables were analyzed using the principal component analysis (PCA). Considering ICDAS scores, 5.62% of the sample had at least an initial decay (ICDAS = 1-2), whereas 40.83% of the sample presented at least one moderate decay (ICDAS = 3-4) and 17.08% a severe decay (ICDAS = 5-6). Decay at ICDAS levels 5-6 and more than 5 missing teeth were statistically associated with Cariogram scores (OR = 2.36, 95%CI = 1.83-3.03 and OR = 1.43, 95%CI = 1.13-1.82, respectively). The results suggest that the Cariogram model was able to identify caries-related factors in an adult population. A direct association among the risk categories from Cariogram, the caries status and some socio-behavioral variables was verified.